Oscillations of the liquid metal flow generated by an alternating magnetic field - Poluyanov, Aleksandr Olegovich; Kolesnichenko, Il′ya Vladimirovich (Computational Continuum Mechanics, 2024)
This paper studies numerically a vortex flow of liquid metal driven by an electromagnetic force, which is generated by the interaction of the alternating magnetic field of a short solenoid with the induced electrical current. A short solenoid is placed coaxially to a cylindrical cell at half of its height. The mathematical model used to describe the process is based on the equations of magnetic hydrodynamics in the induction-free approximation. Calculations, which are carried out by the control volume method using the ANSYS Fluent package, show that the average flow has the form of two toroidal vortices. The calculated velocity fields are indicative of the oscillatory behavior of vortices, accompanied by a change in their sizes. In the examined range of the force parameter, the predominant flow pattern is the single-mode oscillatory flow. The dependences of characteristic frequency and Reynolds number on the force parameter, are obtained using spectral analysis. It has been found that the oscillation period is close to the period of rotation of a large-scale vortex. It has been established that the oscillations are of quasi-periodic character, and a distinct oscillation frequency is observed only in the flow region near the solenoid. The effect of velocity fluctuations is strong and can be detected in laboratory conditions when using gallium eutectic. Such experiment is planned for the near future. The flow rate of gallium eutectic will be measured by an ultrasonic Doppler anemometer. The results of numerical modeling and their verifications can be useful in determining the ways of reducing the intensity of vortex flows during the electromagnetic separation of impurities, which is based on the induction mechanism responsible for the generation of electromagnetic force that displaces particles. The data on the oscillation frequency of the unsteady flow can be used in the development of a non-contact technique for estimating the average electrical conductivity of a two-phase medium, such as a liquid metal with undesirable impurities.